Organophosphorus insecticides: Toxic effects and bioanalytical tests for evaluating toxicity during degradation processes - Čolović Mirjana B.; Krstić Danijela Z.; Vasić Vesna M.; Bondžić Aleksandra M.; Ušćumlić Gordana S.; Petrović Slobodan D. (Hemijska Industrija, 2013)
Organophosphorus insecticides have been the most applied group of insecticides for the last two decades. Their main toxic effects are related to irreversible inactivation of acetylcholinesterase (AChE). Actually, they covalently bind to serine OH group in the enzyme active site forming phosphorylated enzyme that cannot hydrolyze acetylcholine. Organophosphorus insecticides in the environment undergo the natural degradation pathway including mainly homogeneous and heterogeneous hydrolysis (especially at high pH) generating non-inhibiting products. Additionally, thio organophosphates are easily oxidized by naturally present oxidants and UV light, forming more toxic and stable oxons. Thus, oxidative degradation procedures, generally referred as advanced oxidation processes (AOP), have been applied for their efficient removal from contaminated waters. The most applied bioassays to monitor the organophosphate toxicity i.e. the detoxification degree during AOP are Vibrio fischeri and AChE bioassays. Vibrio fischeri toxicity test exploits bioluminescence as the measure of luciferase activity of this marine bacterium, whereas AChE bioassay is based on AChE activity inhibition. Both bioanalytical techniques are rapid (several minutes), simple, sensitive and reproducible. Vibrio fischeri test seems to be a versatile indicator of toxic compounds generated in AOP for organophosphorus insecticides degradation. However, detection of neurotoxic AChE inhibitors, which can be formed in AOP of some organophosphates, requires AChE bioassays. Therefore, AChE toxicity test is more appropriate for monitoring the degradation processes of thio organophosphates, because more toxic oxo organophosphates might be formed and overlooked by Vibrio fischeri bioluminescence inhibition. In addition, during organophosphates removal by AOP, compounds with strong genotoxic potential may be formed, which cannot be detected by standard toxicity tests. For this reason, determination of incidence of micronuclei and cell proliferation index in cultivated human lymphocytes and fibroblasts is suitable for evaluation of organophosphorus insecticides and their break down products inducing cytogenetic damage.